Análise do desempenho térmico em edifícios residenciais: estudo comparativo entre métodos de avaliação para a zona bioclimática 2 - Bisolo, Giovani (Universidade do Vale do Rio dos Sinos, 2018)
The purpose of this study was to evaluate by computational simulation the influence of the constructive characteristics and the orientation in its thermal performance of a housing unit in the Bioclimatic Zone 2, by the norm NBR 15575 and the hour degrees method, in order to understand how these guidelines deal the performance of the building. For this, data on the climatic characterization and the constructive strategies for the Bioclimatic Zone 2 were investigated. The object of this study was a residential building project with four floors, with disposition that allowed to evaluate both the thermal performance of the dormitories facing all the as regards the evaluation of the rooms with opening to the west and south, as required by NBR 15575. For the comparison of the NBR method, 4 days of summer and 4 days of winter were chosen. For comparison of thermal performance by the degree-hour method, all the hours of the year were used. For this study, the base temperature for calculating degree-hours of cooling was 26 ° C and the base temperature for calculating degree-hours of heating was 18 ° C. It can be noticed that the temperature inside the dwelling units was better than those of the external environment, according to the criteria of NBR 15575-1, for all the environments of prolonged residence. For the summer condition, the daily maximum value of the indoor air temperature and for the winter condition were considered, the minimum daily value of the indoor air temperature was considered, both for long stay environments (rooms and dormitories). The results of the simulations evaluated by the criteria of NBR 15575 indicate that vertical fences with concrete blocks or ceramic blocks may have minimum, intermediate and higher levels, or even do not meet the standard, depending on the choice of the typical day for the analysis. The simulated results with thermal load by the degree-hour method, show that thermal performance worsens in summer and winter improves, this shows that inhabited buildings and with the use of equipment, thermal performance can be influenced. At the end of the study, it can be concluded that the simplification of the method of the standard can alter the classification of thermal performance of the building when it indicates only a renewal of air per hour or when it does not allow the inclusion of thermal load, as well as the simplification of the simulation time for only a winter day and a summer day, as there is no parameter of choice for cities that are not listed in the standard. Therefore, it is understood that the analysis of the thermal performance of a building must be elaborated for the whole year.
Keywords: Desempenho térmico; Energy plus; Norma de desempenho; Thermal performance; Energy plus; Performance standard; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo